1997
DOI: 10.1113/jphysiol.1997.sp021897
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced stimulation of murine macrophage chemotaxis: role of corticosterone and prolactin as mediators.

Abstract: 1. Exercise provokes changes in the immune system, including macrophage activity. Chemotaxis is a necessary function of macrophages if they are to reach the focus of infection and strenuous acute exercise may modulate chemotaxis. However, the precise mechanisms remain unknown. 2. Three experiments were performed in the present study. (1) The effect of strenuous acute exercise (swimming until exhaustion) on the chemotactic capacity of macrophages was evaluated. (2) Peritoneal macrophages from control mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 28 publications
0
36
0
3
Order By: Relevance
“…29 Also, PRL stimulates the expression of ICAM-1 in the corpus luteum, 29 and in vitro studies showed that PRL promotes the chemotactic capacity of macrophages. 43 Stimulation of cell adhesion by PRL may involve the activation of integrins LFA-1 and VLA-4, major molecular pathways that mediate firm attachment of leukocytes to vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…29 Also, PRL stimulates the expression of ICAM-1 in the corpus luteum, 29 and in vitro studies showed that PRL promotes the chemotactic capacity of macrophages. 43 Stimulation of cell adhesion by PRL may involve the activation of integrins LFA-1 and VLA-4, major molecular pathways that mediate firm attachment of leukocytes to vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil chemotaxis was evaluated in a Boyden chamber with a modification [11] of the original technique [12], using an isopore polyvinylpyrrolidone-free polycarbonate filter with a pore diameter of 3 µm (Millipore) placed between the two compartments of the chamber. n -formyl-methionyl-leucyl-phenylalanine peptide (10 –8 m , Sigma) diluted in PBS was used as a chemoattractant in the lower compartment of the chamber.…”
Section: Methodsmentioning
confidence: 99%
“…One group has attempted to delineate the mechanism responsible for the exercise-induced increases in chemotaxis 30 and phagocytosis. 37 Their circumstantial evidence points to a hormonal influence perhaps mediated by corticosterone or prolactin and thyroxine, in the case of chemotaxis and phagocytosis, respectively.…”
Section: Monocyte/macrophage Functionmentioning
confidence: 99%
“…They have shown that incubation of macrophages from control animals with plasma from exercised animals stimulates chemotaxis and phagocytosis to similar levels seen in macrophages taken from exercised animals. 30,37 In addition, incubation of macrophages with physiological levels (i.e. plasma levels attained during exercise) of corticosterone, prolactin or thyroxine can stimulate chemotaxis or phagocytosis.…”
Section: Monocyte/macrophage Functionmentioning
confidence: 99%